Properties of a Novel Salmonella Phage L66 and Its Application Based on Electrochemical Sensor-Combined AuNPs to Detect Salmonella - Li, Changbin; Wang, Yuanshang; Wang, Jia; Wang, Xiaohong (Foods, 2022)
Salmonella is widespread in nature and poses a significant threat to human health and safety. Phage is considered as a new tool for the control of food-borne pathogens. In this study, Salmonella phage L66 (phage L66) was isolated from sewage by using Salmonella Typhimurium ATCC 14028 as the host bacterium, and its basic properties were obtained by biological and bioinformatics analysis. Phage L66 had a broad host spectrum, with an optimal infection complex of 0.1 and an optimal adsorption rate of 90.06%. It also exhibited thermal stability between 30 °C~60 °C and pH stability pH from 3 to 12, and the average lysis amount was 46 PFU/cell. The genome sequence analysis showed that the genome length of phage L66 was 157,675 bp and the average GC content was 46.13%. It was predicted to contain 209 genes, 97 of which were annotated with known functions based on the evolutionary analysis, and phage L66 was attributed to the Kuttervirus genus. Subsequently, an electrochemical sensor using phage L66 as a recognition factor was developed and the working electrode GDE-AuNPs-MPA-Phage L66 was prepared by layer-by-layer assembly for the detection of Salmonella. The slope of the impedance was 0.9985 within the scope from 20 to 2 × 107 CFU/mL of bacterial concentration. The minimum detection limit of the method was 13 CFU/mL, and the average spiked recovery rate was 102.3% with a relative standard deviation of 5.16%. The specificity and stability of this sensor were excellent, and it can be applied for the rapid detection of Salmonella in various foods. It provides a phage-based electrochemical biosensor for the detection of pathogenic bacteria.